Review of life history parameters and preliminary age estimates of some New Zealand deep‐sea fishes - Peter J. McMillan; Alan C. Hart; Peter L. Horn; Dianne M. Tracey; Caoimhghin Ó Maolagáin; Brittany Finucci; Matthew R. Dunn (New Zealand Journal of Marine and Freshwater Research, 2021)
A literature review on longevity of New Zealand deep‐sea fishes provided life history parameter estimates for 17 bony and five cartilaginous species. Preliminary age estimates for a further nine deep‐sea bony fishes were made from otolith zone counts and included results from a pilot analysis of radiocarbon age estimates from the otoliths of three of the species. Radiocarbon age estimates corroborated the otolith zone count age estimates made for white rattail ( Trachyrincus aphyodes ) and smallhead cod ( Lepidion microcephalus ) but were substantially lower for the third species, smallscale brown slickhead ( Alepocephalus antipodianus ) which suggested that it was not exposed to elevated (near‐surface) levels of 14 C in early life. Validation of otolith zone age estimates is difficult for deep‐sea species but the radiocarbon analysis provided a practical method to corroborate age estimates for some bony fishes. Of the 31 fish in this study (known and new age estimates), five of the fishery target species and 10 of the bycatch were long‐lived (50 years or more). The hypothesis that all New Zealand deep‐sea species are long‐lived was not supported, but the chance of a species being long‐lived seem to be higher in deeper water.